ANTIBACTERIAL ACTIVITIES OF DIFFERENT ANTISEPTIC SOAPS SOLD IN ABA ON STAPHYLOCOCCUS AUREUS FROM CLINICAL SAMPLES. - C. C., Ike, (IJRDO - JOURNAL OF BIOLOGICAL SCIENCE, 2016)
The antibacterial activity of different types of antiseptic soaps on Staphylococcus aureus isolated from wound infections and eczematous lesions was evaluated. The samples were collected from fifty individuals with wound and eczema infection within the age range of 9-73 years. Swabs were collected and streaked on appropriate agar and incubation temperature. Out of the fifty (50) individuals sampled, 25 persons were mostly infected with Staphylococcus aureus (50% ±1.05) followed by Pseudomonas aeruginosa (22% ±0.91), Staphylococcus epidermis (10% ±0.33) and the least was Escherichia coli (18% ±0.72). This study revealed that Staphylococcus aureus isolated and subcultured were sensitive to the three different antiseptic soaps. The zones of inhibition were highest in sample A with 25.0mm ±0.45 followed by sample B with 20.0mm ±0.98 and least in sample C with 10.0mm ±0.65. The results showed that antiseptic soaps were effective against Staphylococcus aureus involved in wound and eczema infection in humans. Therefore, antiseptic soaps could be used in cleaning the skin during time of hurt or cut, and should be used moderately by consumers to avoid irritation and resistance to pathogens.